“We don’t want to commit as micro-drama creators”: how do these professionals navigate opportunities and internalised prejudices in the evolving micro drama industry - Zhang, Jinwei; Lin, Hui (AoIR Selected Papers of Internet Research, 2026)
This study examines the micro drama industry in China—a sector of online television industry marked by vertically shot, minute-long episodes distributed on mobile platforms—and the paradox of traditional television professionals distancing themselves from micro-drama creation. The research asks why these experienced practitioners disassociate from their micro-drama professionals, what sociocultural implications underpin their sense of “shame,” and how they navigate opportunities amid internalized prejudices in an era defined by platformisation. Employing a multi-method qualitative design that integrates semi-structured interviews with 27 seasoned practitioners, a month-long ethnographic study of a leading production team, and secondary data analysis, the study reveals that the commercialized and formulaic production model—driven by algorithmic gatekeeping and data-driven metrics—intensifies creators’ ambivalence. Findings indicate that while micro dramas offer lucrative and efficient production opportunities, their standardized narratives and reliance on quantitative performance indicators undermine creative legitimacy and contribute to a persistent shame among content creators. This work contributes to digital labour and platform studies by elucidating how algorithmic frameworks and economic imperatives reshape professional identities and creative practices in online television, highlighting the tension between commercial success and artistic recognition in the evolving media landscape.